Le premier temple du travail à Montréal (1907-1938) - Dionne, Jean-Claude (Bulletin du Regroupement des chercheurs-chercheures en histoire des travailleurs et des travailleuses du Québec, 2010)
issued: 2010-23-00
Keywords: Conseil des métiers et du travail de Montréal

La formation en santé et sécurité au travail et la gestion de la qualité proposition pour un système de gestion de la qualité de la formation "C.A.R.T.E." à la Ville de Montréal - Guyon, Christian (École nationale d'administration publique, 2010)

The Long, Angry Summer of ’43: labour Relations in Quebec’s Shipbuilding Industry - Pritchard, James (Labour / Le travail, 2010)
Keywords: Construction navale

La fête du Travail à Montréal le premier lundi de septembre, symbole de l'affirmation de la classe ouvrière dans l'espace public (1886-1952) - Rouillard, Jacques (Revue d'histoire de l'Amérique française, 2010)
issued: 2010-23-00

Sri Lankan Women's Career Identity Evolution after Immigration to Montreal, Quebec, Canada - De Silva, Nilmini (Université McGill, 2010)
Keywords: Femmes; Sri Lankais; Travail

Les procédés discursifs relatifs à l'engagement civique présents dans La Bonne parole , 1939-1951 - Brisebois, Marilyne (Bulletin d'histoire politique, 2010)
issued: 2010-24-00
Keywords: Femmes; Fédération nationale Saint-Jean-Baptiste; Guerre; Travail

Les économies d’agglomération dans les villes nord-américaines: le rôle des travailleurs du haut savoir - Arbour, Sylvie (Institut national de la recherche scientifique - Urbanisation, Culture et Société, 2010)
Keywords: Travail

Entrepreneurs in the New Economy: Immigration and Sex Effects in the Montreal Metropolitan Area - Paré, Sylvie; Therasme, Kelogue (Journal of International Entrepreneurship, 2010)
The recent literature on women’s entrepreneurship shows that they are underrepresented in the main stream economy when compared to their male counterparts, a phenomenon typically observed in other urban contexts. Approximately 30% of the entrepreneurs in the Montreal metropolitan area are women, active in a variety of sectors of the general economy. Their underrepresentation is still greater in the new economy, that is, those sectors that are knowledge-based and/or specialized in information technologies and communications. In this article, we examine the place of female entrepreneurs in the larger economy and in the new economy as related to their immigrant and/or ethnic origins. We seek in this paper to establish a comparative analysis of the situation of women entrepreneurs in immigrant-origin groups, focusing our attention on both the presence of women in entrepreneurial positions and the differential impact associated with membership in an immigrant-origin group. Based on data derived from Scott's Directory of 2007, we first determined an operational definition of the new economy and then analyzed the data from the perspective of sex and ethnic/immigrant origin. New economy enterprises represent approximately 12% of businesses in the Montreal metropolitan area, the majority of which are of the knowledge-based variety, and there is a relative, statistically significant absence of women from such enterprises. At the same time, there is a significantly greater presence of women drawn from minority groups, that is, from groups other than the Anglo-Canadian and French-Canadian dominant groups.
Number: 2
Keywords: Femmes; Travail

A Comparison of Workforce Housing Practices in Three Cities and their Applicability to Montreal - Lazarovic, Rebecca (Université McGill, 2010)
Keywords: Logement; Travail

Girl Watching at Expo 67 - Wallace, Aurora (Expo 67: Not Just a Souvenir, 2010)

Solemn Processions and Terrifying Violence: Spectacle, Authority, and Citizenship during the Lachine Canal Strike of 1843 - Horner, Dan (Urban History Review / Revue d'histoire urbaine, 2010)
Number: 2
Keywords: Grèves; Irlandais; Lachine (canal)

Programme d'intégration pour les agents administratifs de l'Hôpital du Sacré-Cœur de Montréal - Majeau, Linda (École nationale d'administration publique, 2010)
Keywords: Hôpital du Sacré-Coeur; Hôpitaux

La contribution juive à la sphère économique et syndicale jusqu'à la Deuxième Guerre mondiale - Dansereau, Bernard (Les communautés juives de Montréal. Histoire et enjeux contemporains, 2010)
Keywords: Juifs

Les trajectoires de l'intégration professionnelle des immigrants iraniens travaillant comme chauffeurs de taxi à Montréal - Namazi, Vahideddin (Université de Montréal, 2010)
Keywords: Iraniens

Aspects démographiques de la vie des couturières de Montréal au XVIIIe siècle - Gousse, Suzanne (Cahiers d'histoire, 2010)
issued: 2010-24-00
Keywords: Confection; Femmes